Phyto-additive effects of baobab (Adansonia digitata l.) fruit pulp on physiological, reproductive and antioxidant indices of male Japanese quail (Coturnix coturnix japonica) - Amao, O. A.; Hammed, O. O; Olugbade, B. O.; Amao, J. P. (ADAN JOURNAL OF AGRICULTURE, 2025)
A 12-week experiment was carried out to investigate the effect of varying levels of Baobab Fruit Pulp (BFP) on the haematological and serum biochemical parameters, testicular morphometrics, reproductive hormones and antioxidant indices of male Japanese quails (Coturnix coturnix japonica). Eighty (80) male Japanese quails (4 weeks old) were used for the experiment. The quails were randomly allotted to five dietary treatments T1, T2, T3, T4 and T5 of 16 birds each with two replicates in a Completely Randomized Design (CRD). The control diet was tagged T1 and did not contain BFP while T2, T3, T4 and T5 contained 0.2, 0.4, 0.6 and 0.8% BFP respectively. At the end of the 12th week, blood samples were collected for haematological, serum biochemical, reproductive hormones and oxidative stress indices assays. The birds were sacrificed and testes were carefully dissected for testicular morphometrics (testes weight, length and volume). Data were analyzed using ANOVA at p<0.05. The quails’ packed cell volume, red blood cell, mean corpuscular volume, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration were all significantly (p<0.05) higher at 0.8% BFP supplementation level than other levels. Aspartate aminotransferase, Alanine aminotransferase, Low density lipoprotein, High density lipoprotein and urea were also significantly (p<0.05) higher at 0.8% BFP than other levels. Quails fed 0.2% BFP had significantly (p<0.05) larger mean testes volume than other treatments. Follicle stimulating hormone was significantly higher at 0.2 and 0.4% BFP than other treatments while glutathione was highest at 2% BFP. It was concluded that up to 0.8% BFP supplementation supported blood formation but could lead to liver and kidney damage. However, 0.2% supplementation showed the potential to enhance reproductive parameters and antioxidant indices of the male Japanese quail without adverse effect.